Utz Richsner as Ideologue of the Schilling Uprising in Augsburg, 1524 - Bast, Robert J. (Renaissance and Reformation / Renaissance et Réforme, 2017)
The 1524 uprising of evangelical artisans in Augsburg on behalf of the Franciscan preacher Johann Schilling counts as a turning point of the Reformation movement in that city. Relying on chronicles, government reports, and interrogation records, previous scholarship—none better than Jörg Rogge’s—has exposed the egalitarian theology and the social, economic, and political critique that united Schilling’s supporters. Yet the source of their ideology has always been unclear, for Schilling left behind neither treatises nor sermon transcriptions. That lacuna can be filled in part by re-examining sources largely overlooked: the four pamphlets published in 1524 by the weaver Ulrich (Utz) Richsner. A contextual reading of those pamphlets suggests a close collaboration between Schilling and Richsner, and a much more central role for Richsner in the movement around Schilling than has yet been recognized.